Numerical Mathematics and Advanced Applications - ENUMATH 2013: Proceedings of ENUMATH 2013, the 10th European Conference on Numerical Mathematics and Advanced Applications, Lausanne, August 2013 - Abdulle, Assyr; Deparis, Simone; Kreßner, Daniel; Nobile, Fabio; Picasso, Marco (Lecture Notes in Computational Science and Engineering, 2015)
Preface -- Part I: Space Discretisation Methods for PDEs -- Part II: Time Integration Schemes -- Part III: A Posteriori Error Estimation and Adaptive Methods -- Part IV: Numerical Linear Algebra -- Part V: Multiscale Modeling and Simulation -- Part VI: Reduced Order Modeling -- Part VII: Optimal Control -- Part VIII: Uncertainty, Stochastic Modeling and Applications -- Part IX: Solvers, High Performance Computing and Software Libraries -- Part X: Computational Fluid and Structural Mechanics -- Part XI: Computational Electromagnetics